‘Urmitella timonensis’ gen. nov., sp. nov., ‘Blautia marasmi’ sp. nov., ‘Lachnoclostridium pacaense’ sp. nov., ‘Bacillus marasmi’ sp. nov. and ‘Anaerotruncus rubiinfantis’ sp. nov., isolated from stool samples of undernourished African children - Pham, T.-P.-T. (New Microbes New Infect, 2017)
We report here the main characteristics of five new species ‘Urmitella timonensis’ strain Marseille-P2918(T) (CSUR P2918), ‘Blautia marasmi’ strain Marseille-P2377(T) (CSUR P2377), ‘Lachnoclostridium pacaense’ strain Marseille-P3100(T) (CSUR P3100), ‘Bacillus marasmi’ strain Marseille-P3556(T) (CSUR P3556) and ‘Anaerotruncus rubiinfantis’ strain MT15(T) (CSUR P2276), which were isolated recently from stool samples taken from undernourished children in Niger and Senegal using microbial culturomics.